GE_GERICHTE P/23340/2022 vom 16. Oktober 2025 - GE Cour de justice (2025)
IN DUBIO PRO REO;DISPOSITIONS PÉNALES DE LA LEI;USAGE DE FAUX(DROIT PÉNAL);DOL ÉVENTUEL | LEI.115.al1.letb; LEI.115.al1.letc; LEI.118.al1; CP.252